Participatory budgeting: creator or creation of a better place? Evidence from rural Poland - Leśniewska-Napierała Katarzyna; Napierała Tomasz (Bulletin of Geography. Socio-Economic Series, 2020)
The main purpose of the research is to address the real, operational context of participatory budgeting. It is argued that this method of budgeting might be a useful tool for developing various ideas at a local level, including social/spatial justice, civil society, human capital, information society, or sustainable development. However, the implementation of participatory budgeting might, conversely, result from development processes. A combination of quantitative methods (principal component analysis and regression analysis) was applied to define the real motives for local authorities to employ participatory budgeting. To address the research questions mentioned in the paper, all rural communes employing participatory budgeting in Poland in 2017 were investigated. It was confirmed that participatory budgeting is an effect of development processes rather than a tool for achieving development goals. Interestingly, social/spatial injustice might significantly stimulate inhabitants’ engagement in participatory budgeting. On the other hand, the development of information society supports processes related to social involvement, including participatory budgeting.